What is The Role of Genetic Predisposition in Gestational Trophoblastic Disease ? : A Systematic Review - Bangar Parlinggoman Tua; Yahya Nurlianto (International Medical Journal Corp. Ltd, 2025)
Introduction : Gestational Trophoblastic Disease (GTD) encompasses a spectrum of proliferative placental disorders. While genetic alterations are integral to its pathogenesis, the role of inherited genetic predisposition remains poorly quantified. A significant gap exists between the established use of genetic markers for diagnostics and a comprehensive understanding of heritable risk. This systematic review aims to synthesize the current evidence on the role of genetic predisposition in GTD. Methods : Adhering to PRISMA 2020 guidelines, a systematic literature search was conducted across PubMed, Semantic Scholar, Springer, and Google Scholar. Eligibility criteria focused on studies investigating genetic variants, hereditary factors, or familial clustering in human subjects with any form of GTD. Data on genetic analysis types, specific markers, predisposition findings, and clinical implications were systematically extracted and synthesized. Results : From 11 included studies, the evidence for inherited predisposition was limited and heterogeneous. Strong evidence was confined to recurrent hydatidiform moles, with one systematic review identifying monogenic causes involving genes such as NLRP7, CHRNA1, DYNC2H1, and RYR1. Other studies documented molecular dysregulation in genes like p53 and BCL-2 without quantifying inherited risk. A prominent theme was the diagnostic utility of genetics, with SNP arrays, STR analysis, and cell-free DNA being used for diagnosis and differentiation rather than risk prediction. No high-level evidence for predisposition was identified. Discussion : The evidence confirms a clear heritable, monogenic cause for a subset of patients with recurrent molar pregnancies. However, for sporadic GTD, research has pivoted towards diagnostic applications that improve disease detection and management, rather than establishing quantifiable predisposition risk. While genetic tools for diagnostics are advancing, their application for risk assessment remains limited. Conclusion : The clinical role of genetics in GTD is currently centered on diagnosis rather than risk prediction. While heritable factors are definitive in rare recurrent cases, quantifiable genetic risk for the broader population remains largely unknown. Future research requires large-scale association studies to identify risk alleles and translate molecular insights into prognostic and therapeutic strategies for all forms of GTD.